PEMBANGUNAN PROTOTIPE SMS SERVER UNTUK VEHICLE TRACKING - Andi Leo (Business Management Journal, 2017)
Safety factor has become one of the most fundamental needs in everyday life. People make use several ways in order to safeguard their moveable goods, such as  motorcycle and vehicles. GPS Satellite in one of the solutions that can monitor the position of the moveable assets and the satellite information may in turn assist the users to locate the positions of their vehicles. One main reason why the individual user does not use the information is due to the relatively high price of the equipment. Through the technological advances and tough competition, one alternative at hand is cellular phones to be used to monitor the vehicles at a much more considerable price.Based on acquired sources, gradual analysis is conducted regarding the need for ideal hardware and maximum software through Vehicle Tracking System (VTS). Design of protoype of SMS Server for data Processing from VTS is prepared to provide information about the vehicle position for the users assumed to have been previously registered. The information can solely be acquired by the users through request in SMS, sent to certain operator with predetermined format.Owing to limited time and cost, the implementation merely uses the wares that can presumbly represent the needed hardware of software. In the try out, several scenarios to be used had already been available in order to test whether the design prototype of SMS Server in place can contribute a suitable feedback/ response corresponding with the sent request by customers to the “operator”.Of the several availabe scenarios are provided from various conditions, output gained by customer by using cellular phone can bring about some effective and effecient advantages.Keyword : Safety, Vehicle, GPS Satellite, Cellular Phone